The Royal Inscriptions of Esarhaddon, King of Assyria (680-669 BC) - Leichty, Erle (2011)
with a contribution by Grant Frame and the editorial Assistance of Jamie Novotny, Matthew T. Rutz, and Amy E. Barron.